Electron‐Beam‐Induced Adatom‐Vacancy‐Complexes in Mono‐ and Bilayer Phosphorene - Carsten Speckmann; Andrea Angeletti; Lukáš Kývala; David Lamprecht; Felix Herterich; Clemens Mangler; Lado Filipovic; Christoph Dellago; Cesare Franchini; Jani Kotakoski (Advanced Materials Interfaces)
Abstract Phosphorene, a puckered 2D allotrope of phosphorus, has sparked considerable interest in recent years due to its potential especially for optoelectronic applications with its layer‐number‐dependant direct band gap and strongly bound excitons. However, detailed experimentalcharacterization of its intrinsic defects as well as its defect creation characteristics under electron irradiation are scarce. Here, the creation and stability of a variety of defect configurations under 60 kV electron irradiation in mono‐ and bilayer phosphorene are reported including the first experimental reports of stable adatom‐vacancy‐complexes. Displacement cross section measurements in bilayer phosphorene yield a value of 7.7 ± 1.4 barn with an estimated lifetime of adatom‐vacancy‐complexes of 19.9 ± 0.7 s, while some are stable for up to 68 s under continuous electron irradiation. Surprisingly, ab initio‐based simulations indicate that the complexes should readily recombine, even in structures strained by up to 3%. The presented results will help to improve the understanding of the wide variety of defects in phosphorene, their creation, and their stability, which may enable new pathways for defect engineered phosphorene devices.